Luck versus Skill in the Cross Section of Mutual Fund Returns: Reexamining the Evidence - HARVEY, CAMPBELL R.; LIU, YAN (Journal of Finance, 2022)
ABSTRACT While Kosowski et al. (2006, Journal of Finance 61, 2551–2595) and Fama and French (2010, Journal of Finance 65, 1915–1947) both evaluate whether mutual funds outperform, their conclusions are very different. We reconcile their findings. We show that the Fama‐French method suffers from an undersampling problem that leads to a failure to reject the null hypothesis of zero alpha, even when some funds generate economically large risk‐adjusted returns. In contrast, Kosowski et al. substantially overreject the null hypothesis, even when all funds have a zero alpha. We present a novel bootstrapping approach that should be useful to future researchers choosing between the two approaches.